Kahoot! in English Language Learning: University Students' Perceptions and Challenges Explored - Addhiny, Tuning (International Journal of English and Applied Linguistics (IJEAL), 2024)
This qualitative case study investigates university students' perceptions and challenges related to the use of Kahoot! in English language learning. The study focuses on understanding how students perceive Kahoot! as a learning tool and the main challenges they face while using it. A total of 90 participants, consisting of 20 students from IAHN Gde Pudja Mataram and 70 from UIN Mataram, were purposively selected based on their experience with Kahoot in English courses. Data were collected through closed and open-ended questionnaires to provide a comprehensive understanding of their experiences. The findings indicate overwhelmingly positive perceptions of Kahoot!, with participants expressing enthusiasm for its engaging format and its effectiveness in enhancing understanding of English language concepts. Qualitative responses highlighted how Kahoot! makes learning enjoyable and motivating, while the competitive aspect was seen as a valuable component of the learning experience. However, some challenges were identified, primarily related to internet connectivity and the pacing of questions. Despite these challenges, the overall sentiment suggests that the benefits of using Kahoot! in higher education contexts significantly outweigh the difficulties encountered. This study contributes to the growing body of research on gamification in language learning, emphasizing the potential of interactive tools like Kahoot! to enhance student engagement and learning outcomes in English language education. Keywords: Challenges, English Language Learning, Gamification, Kahoot!, Perception